Unusual Initial Presentation of Herpes Simplex Virus as Inguinal Lymphadenopathy - Sarah A. Fleming; John G. Strickler (Hindawi Limited, 2015)
Genital herpes simplex virus (HSV) infections are a common cause of inguinal lymphadenopathy. However, surgical excision of enlarged inguinal nodes is almost never performed to initially diagnose genital herpes simplex virus, due to the distinct external presentation of genital herpetic vesicles that usually occur with the first symptoms of infection. Therefore, the histologic and immunophenotypic features of HSV-associated inguinal lymphadenopathy are unfamiliar to most pathologists. The current report describes the lymph node pathology of two immunocompetent patients, whose initial HSV diagnosis was established through surgical excision of enlarged inguinal lymph nodes. Histologic examination showed features consistent with viral lymphadenopathy, including florid follicular hyperplasia, monocytoid B-cell hyperplasia, and paracortical hyperplasia without extensive necrosis. Immunohistochemical stains for HSV antigens, using polyclonal anti-HSV I and II antibodies, demonstrate strong immunoreactivity for HSV in a small number of cells in the subcapsular sinuses, especially in areas with monocytoid B-cell hyperplasia. Rare scattered HSV-positive cells also are identified in paracortical areas and germinal centers. We conclude that an initial diagnosis of genital HSV infection may be established by inguinal lymph node biopsy.